An Ordinance Relating to Misdemeanors, § 41, in The Act of Incorporation and Ordinances of the City of Bunker Hill, Illinois 66 (1873). - (:unkn) unknown (My University, 1873)
Any person or persons who shall, within said city, draw on any person or persons, to the terror or danger of such person or persons, any knife, bowie knife, pistol, revolver, slung shot, or any other dangerous weapon, shall forfeit and pay the sum of not less than twenty-five dollars.
Keywords: BRANDISHING